Pengaruh Ta’zir Terhadap Akhlak Santri Putri Pondok Pesantren - Difa Ilwa Dilia; Rony Rony; Anis Trianawati (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2022)
The purpose of this article was to determine how the influence of ta'zir on the morals of female students at Mamba'ul Hikmah Islamic Boarding School Dlanggu Mojokerto. This type of research is quantitative research with a survey approach. The instrument used is a questionnaire and uses a Likert scale with four alternative answers to answer. The research sample was 57 female students from a population of 135 female students. The results showed that there was an influence on the application of ta'zir to the morals of female students of the Mamba'ul Hikmah Islamic Boarding School Dlanggu Mojokerto. This is based on the results a simple regression analysis, it is known that t count = 4.537, the regression coefficient (b) is 0.806 with a significance value of 0.000 <0.05, which means Ho is rejected and Ha is accepted. From the research that has been done, it can be concluded that there is an influence of ta'zir on the morals of female students at Mamba'ul Hikmah Islamic Boarding School Dlanggu Mojokerto. It is known that the coefficient of determination (R Square) is 0.272, which means that the influence of the Ta'zir variable (X) on the female student morality variable (Y) is 27.2%.